Eksekusi Jaminan Fidusia Yang Tidak Didaftarkan Dalam Likuidasi Bank - Setiadi, Wahyu Tantra; Landra, Putu Tuni Cakabawa (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this study is to find out the procedure for registering fiduciary guarantees, to analyze the legal consequences of bank liquidation on fiduciary guarantees and to analyze the execution of fiduciary guarantees that are not registered in bank liquidation. This article used normative juridical research method. The results of the study show that (1) The procedure for registering a fiduciary guarantee is divided into two stages, namely the imposition stage and the registration stage of the fiduciary guarantee and then the guarantee is registered online by accessing the online AHU site to issue a fiduciary guarantee certificate. (2) The legal consequences of bank liquidation on fiduciary guarantees, then all bank operational activities will be stopped due to the revocation of banking business licenses and accelerate the collection of debtor credit debts which are authorized by the Deposit Insurance Corporation. (3) Execution of fiduciary guarantees that are not registered in bank liquidation can still be executed guarantees, the most important thing is that the non-registration of fiduciary guarantees is the negligence of the creditor. Therefore, creditors represented by the liquidation team must be able to prove that there is a debtor who is in default and if the debtor still does not acknowledge the existence of a default, the liquidation team must take legal action with a lawsuit against the court related to default and if proven, then a court decision that has permanent legal force can execute a fiduciary guarantee object.